Linkage Between Hospital Accessibility and Health Insurance Ownership in East Kalimantan Province - Rahayu, Eka Putri; Ariyanti, Rea; Rahayu, Agustin Putri (BPJS Kesehatan, 2025)
Healthcare accessibility remains a persistent challenge in Indonesia, particularly in resource-limited regions where geographical barriers, transportation constraints, and financial limitations create significant disparities in health service utilization. Hospital accessibility encompasses multiple dimensions that collectively influence healthcare utilization patterns. The physical presence of healthcare facilities, commonly referred to as hospital existence, serves as the fundamental prerequisite for healthcare access. This study seeks to analyze how dimensions of hospital accessibility correlate with health insurance ownership in East Kalimantan. 2023 Indonesian Health Survey. This research was quantitative approach with cross sectional design. The population in this research refers to the population of 2023 Indonesian Health Survey, with total . Chi square analysis was used to determine the relationship between the independent variable and dependent variable. The result shows that the independent variables that are significantly related to the health insurance ownership with p-value < 0.005, namely marital status, age group, education level and occupation. Meanwhile, sex (p-value= 0.185), residence (p-value= 0.093) and hospital accessibility (p-value= 0.134) showed no significant associations with health insurance ownership with p-value > 0.005. The lack of association between hospital accessibility and insurance ownership indicates that physical proximity to healthcare facilities is not a primary determinant of insurance enrolment decisions.